Unstable thin film spreading of volatile binary mixtures - Isojärvi, Teemu (2013)
This Thesis discusses the fluid mechanics of thin films, with emphasis on dynamical instabilities observed in some situations. The theoretical part first presents the main theory of thin-film flow, and then advances to discuss the problems associated with incorporation of evaporative effects and binary mixtures in the model. In the experimental part, measurements related to spreading of certain class of binary mixtures are presented. The studied mixtures have a volatile component with low surface tension and a less volatile component with high surface tension. The main example of such a mixture is the water-isopropanol system.